The Body from The Perspective of Pierre Bourdieu: A Theoretical Study - Shahlaa Wali Jabbar; Dunya Salahdin Mirdan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Pierre Bourdieu discussed a number of issues that led to a critical direction in sociology. One of the most controversial topics in Bourdieu’s thought is the body. The subject of this study is to identify the social contexts of the body beyond the fact that the body is a biological given, the cultures of different societies play a role in the emergence and development of that biological currency. The manifestation of the body in the context of cultural capital, explanation of the body as an indicator of class differences and as a carrier of social memory. The aim of this study is to highlight Pierre Bourdieu’s thinking on the issue of the body and link it to other elements of society such as social class and capital, then revealing that side of the body when it becomes the history of the individual and society as a whole. According to Bourdieu, the body is a socially shaped entity that connects the individual to her/his social and cultural context. The body also creates part of cultural capital. The body is also a means of social difference, and physical traditions are sufficient for the habitus of the individual, finally, the body plays an important role in shaping society’s memory, somehow physical traditions become history, that is, the body is a living history that walks on earth.